Internet connectivity disruption in Congo (Congo) - Voidly (2026)
CRITICAL severity disruption detected in Congo. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: CG-2026-0012
Keywords: internet disruption; CG; disruption; critical